2011
DOI: 10.1007/s10610-011-9158-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prison Staff on Inmate Conditions: A Multilevel Approach to Staff and Inmate Surveys

Abstract: The current study connects survey data of inmates and correctional staff in the Dutch prison system in order to describe and explain the impact of staff orientation and staff working conditions on perceived prison circumstances of inmates. Importation and deprivation theory are combined to test an integrated model to explain perceived prison conditions. By surveying staff (N=1750) and inmates (N=4673) independently within the same period of time and by afterwards pairing the results on the level of the housing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 44 publications
4
40
0
4
Order By: Relevance
“…This means that respondents would report a state of affairs while knowing reality is different. However, other research suggests that survey results in prisons (both inmate and staff) vary in a systematic way across facilities (Camp, 1999;Camp et al, 2002;Molleman, 2008;Molleman & Leeuw, 2012). Survey data have been shown to be consistent with official prison records (Dagget & Camp, 2009;Molleman, 2011).…”
Section: Closing Remarksmentioning
confidence: 99%
“…This means that respondents would report a state of affairs while knowing reality is different. However, other research suggests that survey results in prisons (both inmate and staff) vary in a systematic way across facilities (Camp, 1999;Camp et al, 2002;Molleman, 2008;Molleman & Leeuw, 2012). Survey data have been shown to be consistent with official prison records (Dagget & Camp, 2009;Molleman, 2011).…”
Section: Closing Remarksmentioning
confidence: 99%
“…Abordagens multinível: a complexidade do estudo de variáveis psicológicas em contexto prisional poderá ser acompanhada de abordagens metodológicas que representam essa mesma complexidade. Nesse sentido, o estudo do comportamento humano em contexto prisional poderá incorporar, através da recolha e análise de dados em múltiplos níveis de análise, a relação com variáveis de nível grupal ou organizacional (e.g., Camp, Gaes, Langan, & Saylor, 2003;Camp & Gaes, 2005;Lahm, 2007;Molleman & van der Broek, 2014;Molleman & van Ginneken, 2015;Molleman & Leeuw, 2012;Morris & Worrall, 2010;Wooldredge, Griffin, & Pratt, 2001).…”
Section: Considerações Finais E Implicações Para a Investigação Futuraunclassified
“…Harer and Steffensmeier (1996) reported that a high proportion of staff who have positive attitudes towards inmates is negatively associated with prison violence. This result might be related to the finding that prisoners experience less strain if prison staff have a favourable orientation towards working with the inmates (Molleman and Leeuw, 2012). Liebling (2011) and Crewe et al (2011) have also stressed the importance of a good relationship between prison officers and inmates in maintaining order and thus preventing prison violence.…”
Section: Deprivation Factorsmentioning
confidence: 99%